2007
DOI: 10.1016/s1726-4901(07)70002-3
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Therapy Results in Immediate Bronchodilating Effect in Asthma Patients

Abstract: In asthma patients, acupuncture treatment may result in immediate improvement of FEV1, but the degree of improvement is less than that from inhalation bronchodilator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 8 publications
1
17
0
1
Order By: Relevance
“…Needling at distant non-acupoints with superficial insertion is another commonly applied sham acupuncture procedure [12][13][14][15][16][17][18] . Two trials on acupuncture for intractable epilepsy provided examples of this kind of sham control [19,20] .…”
Section: Needling At Distant Non-acupointsmentioning
confidence: 99%
“…Needling at distant non-acupoints with superficial insertion is another commonly applied sham acupuncture procedure [12][13][14][15][16][17][18] . Two trials on acupuncture for intractable epilepsy provided examples of this kind of sham control [19,20] .…”
Section: Needling At Distant Non-acupointsmentioning
confidence: 99%
“…The herbal mixture applied on the acupoints could regulate ‘Qi' and improve pulmonary function [30,31]. Some studies showed that acupuncture also had beneficial effects on the pulmonary function of patients with asthma [32,33]. Carneiro et al [34 ]reported that the stimulation provided by acupuncture (Fei Shu ‘BL 13') could lead to the improvement of lung inflammation and cellular inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Chu et al reported 3 cases of immediate bronchodilation following acupuncture. 11 It could be argued that the response was the result of nonspecific psychologic factors, but psychologic factors causing wheezing are rare in children. Such quick responses are useful in the acute stage, but, to…”
Section: Discussionmentioning
confidence: 99%
“…All the treatment steps described are according to Chinese Medicine principles. In the acute phase, when a patient is seen while wheezing, acupuncture alone has been effective for relieving wheezing in the majority of cases as shown by Chu et al 11 The success of treatment will depend on the correct selection of points, especially in chronic cases, based on the underlying Disharmony pattern. Combination patterns are common.…”
Section: Sudhakaranmentioning
confidence: 99%